2017
DOI: 10.1177/1932296817728525
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Meal Insulin and Its Relation to Adherence to Therapy in Type 1 Diabetes

Abstract: The purpose of this study is to examine timing of meal insulin and further determine whether an association exists between timing of meal insulin and missed meal insulin doses. The cohort included 4768 T1D Exchange clinic registry participants <26 years with type 1 diabetes ≥1 year. Chi-square tests, t-tests, and regression were used to assess the relationship between participant characteristics and timing of meal insulin and missed meal doses, respectively. Timing of meal insulin and association with missed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 11 publications
0
26
0
Order By: Relevance
“…The majority of children in this cohort routinely give insulin before meals, which has been shown to be an important factor in minimizing postmeal glycemic excursions 31. In addition to a study that previously demonstrated a decrease in HbA1c by the administration of preprandial versus postprandial insulin,32 a recent study using T1D Exchange Clinic registry data reported a association between preprandial insulin dosing and lower HbA1c 33. However, as opposed to our small sample where 95% gave insulin before meals, only 61% of 419 parents/carers surveyed in the T1D Exchange gave insulin before the meal, suggesting that this may be an area of concern for health providers and parents alike.…”
Section: Discussionmentioning
confidence: 96%
“…The majority of children in this cohort routinely give insulin before meals, which has been shown to be an important factor in minimizing postmeal glycemic excursions 31. In addition to a study that previously demonstrated a decrease in HbA1c by the administration of preprandial versus postprandial insulin,32 a recent study using T1D Exchange Clinic registry data reported a association between preprandial insulin dosing and lower HbA1c 33. However, as opposed to our small sample where 95% gave insulin before meals, only 61% of 419 parents/carers surveyed in the T1D Exchange gave insulin before the meal, suggesting that this may be an area of concern for health providers and parents alike.…”
Section: Discussionmentioning
confidence: 96%
“…As technology evolves, so must our measurement of self-management behaviors. Adherence to CGM and insulin pump use has typically been examined in the context of number of days of wear in the former [46, 47] and missed boluses in the latter [48, 49]. A comprehensive list of individual self-management tasks for CGMs (e.g., respond to alerts) and insulin pumps (e.g., carrying supplies, counting carbohydrates, administering boluses, checking blood glucose) has been described by Tanenbaum and colleagues [50].…”
Section: Biopsychosocial Factors Associated With Cgm and Insulin Pumpmentioning
confidence: 99%
“…Present therapy relies on subcutaneous insulin to suppress HGP, a role it is pharmacokinetically poorly suited for, and to stimulate glucose disposal in peripheral tissues. Further, many patients wait until after eating to deliver a subcutaneous insulin bolus, which exacerbates this PK mismatch and worsens postprandial hyperglycaemia . Adding tregopil as an adjunct to rapid‐acting subcutaneous insulin could transfer the responsibility of inhibiting HGP from subcutaneous insulin to tregopil.…”
Section: Discussionmentioning
confidence: 99%
“…Further, many patients wait until after eating to deliver a subcutaneous insulin bolus, which exacerbates this PK mismatch and worsens postprandial hyperglycaemia. 29 Adding tregopil as an adjunct to rapid-acting subcutaneous insulin could transfer the responsibility of inhibiting HGP from subcutaneous insulin to tregopil. Because tregopil more closely approximates rapid, physiological insulin release, during the 5-hour postprandial period.…”
mentioning
confidence: 99%